Edukasi Tentang Pentingnya Pemeriksaan Antenatal Care (Anc) Pada Ibu Hamil - Siti Komariyah siti; Aurelia Intan Fitriani Fitriani (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2022)
The health of pregnant women is one of the national health indicators. So that reducing maternal mortality is one of the eight goals formulated in the international Millennium Development Goals (MDGs) commitment for the long-term development of Indonesia's health from 2005 to 2025. Antenatal care (ANC) is a health facility that is preventive care developed with The aim is to prevent and reduce complications for pregnant women. However, the importance of ANC visits has not been a top priority for some pregnant women regarding their pregnancies in Indonesia. So that the program or antenatal care is a place that is made to control the condition of the mother during pregnancy as early as possible. So it is necessary to educate pregnant women, this activity aims to increase the knowledge of pregnant women. This community service is carried out by counseling about the importance of ANC. The subjects of the service were 27 pregnant women. The result of this activity is that the mother's knowledge increases. With this activity, it is hoped that pregnant women will continue to pay attention to their health.